Flemish School Boards’ Reasons for (Not) Organising Snow Classes (Baltic Journal of Sport and Health Sciences, 2026)
Introduction: For some decades, snow classes (SC) in the Alps have been an optional activity in Flemish primary and secondary schools. However, winter sports are recognised as both a motor and victim of climate change. Transport, intense reliance on infrastructure and equipment, land use, maintenance of slopes, and providing acceptable (artificial) snow conditions create a considerable ecological impact, and at the same time clarify why winter sports are relatively expensive. The aim of the present study was to gain insight into school boards’ reasons for (not) organising SC in Flemish primary and secondary schools, now and in the coming years.Methods: An online questionnaire using Qualtrics software was sent out to all Flemish primary and secondary schools in Flanders and the Brussels-Capital Region (n = 3,362). Questions were categorised into: 1) barriers, 2) SC modalities and activities, 3) expectations for future SC.Results: Response rate was 7.8% (n = 262). The majority (n = 188, 72%) declared not to organise SC but 76 of these schools had considered it and abstained from organising, reporting the following barriers: ‘expensive’ (95%), ‘high ecological footprint’ (22%), ‘safety concerns’ (21%), ‘organisational complexity’ (21%), ‘lack of qualified staff’ (20%), ‘no pedagogical added value’ (11%), ‘little student interest’ (9%). SC-organising schools reported the following barriers: ‘expensiveness’ (90%), ‘lack of qualified staff’ (39%), ‘safety concerns’ (26%), ‘unforeseen conditions (e.g. no snow)’ (13%), ‘organisational complexity’ (12%), and ‘ecological footprint’ (2%). SC are organised annually or biennially and last 6–10 days, costing students between